ARIS-The Augmented Reality Studio - Nabeel AbuBaker; Firas Dwiekat (My University, 2014)
ARIS Augmented reality studio is a tool for creating and publishing AR based applications. The importance of this project comes from the fact that many companies and individuals are moving their software development scheme toward augmented reality especially after the successful experience of Google glass and the evolution of high performance smart phones.In this project, we will develop a tool to ease the process of creating a smart phone, tablet or desktop applications using a friendly user interface with providing the most developed features that can be offered by AR SDKs.Our main objectives of this project: To develop a studio that facilitates the creating of AR applications for normal users (non-developers). To combine the most recent and developed features offered by different free SDKs. Output a high quality application with the ability to select a specific platform.In this project, we will start with the core application which will consist of the SDK/SDKs for both the AR and the platforms we will support (e.g. Android, iOS) and the process of creating and compiling the application using those SDKs. Then we will build a friendly user interface to communicate with the core application to make use of its features.There are some desktop and web-based tools similar to our application but they are either support simple features or for a